2004
DOI: 10.1086/381001
|View full text |Cite
|
Sign up to set email alerts
|

Variation in a Repeat Sequence Determines Whether a Common Variant of the Cystic Fibrosis Transmembrane Conductance Regulator Gene Is Pathogenic or Benign

Abstract: An abbreviated tract of five thymidines (5T) in intron 8 of the cystic fibrosis transmembrane conductance regulator (CFTR) gene is found in approximately 10% of individuals in the general population. When found in trans with a severe CFTR mutation, 5T can result in male infertility, nonclassic cystic fibrosis, or a normal phenotype. To test whether the number of TG repeats adjacent to 5T influences disease penetrance, we determined TG repeat number in 98 patients with male infertility due to congenital absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
199
7
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(235 citation statements)
references
References 9 publications
21
199
7
8
Order By: Relevance
“…13 TG11-5T was by far the most common in United States, Czech Republic, Poland, Italy and Germany populations, followed by TG12-5T and TG13-5T. 13 However, our study showed that TG11-5T was not found in the normal Chinese population ( Table 4). Ethnic differences in the incidence of CFTR (TG)m(T)n around the world are quite striking.…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688contrasting
confidence: 48%
See 3 more Smart Citations
“…13 TG11-5T was by far the most common in United States, Czech Republic, Poland, Italy and Germany populations, followed by TG12-5T and TG13-5T. 13 However, our study showed that TG11-5T was not found in the normal Chinese population ( Table 4). Ethnic differences in the incidence of CFTR (TG)m(T)n around the world are quite striking.…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688contrasting
confidence: 48%
“…13 In 72 cases with 97 alleles of IVS8-5T present in 109 Chinese CBAVD patients, 70 cases (97.22%) and 94 alleles (96.91%) had 12 or 13 TG repeats adjacent to 5T. TG12-5T was the most common disease-associated combination, and was found in 33.94% of the Chinese CBAVD patients versus 13.46% of controls ( Table 4).…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688mentioning
confidence: 98%
See 2 more Smart Citations
“…Haplotypic backgrounds, including variations in introns, have been known to influence the severity of an associated phenotype caused by an exonic variant. 39 TGIF is a member of the TALE superclass of homeobox proteins. The genes encoding these proteins are highly conserved in different species.…”
Section: Resultsmentioning
confidence: 99%